Effect of Additives on the in situ Laccase-Catalyzed Polymerization of Aniline Onto Bacterial Cellulose - Shim, Euijin; Noro, Jennifer; Cavaco-Paulo, Artur; Silva, Carla; Kim, Hye Rim (Frontiers in Bioengineering and Biotechnology, 2019)
Laccase-mediated systems are a green route to accelerate the oxidation of aniline and obtain polyaniline with conductive properties. The synthesis of green polyaniline (emeraldine salt) was herein improved by the inclusion of additives like sodium bis (2−ethyl hexyl) sulfosuccinate (AOT) and potassium hexacyanoferrate (Ⅱ) (KHCF) in the medium. The aniline polymerization was confirmed by the detection of the absorption band typical of emeraldine salt at 420 nm, typical of the semiquinoid radical cation, and of the polaron absorption band at 700-800 nm, corresponding to the distinctive signal of doped or partial doped aniline. The oligomers and/or polymers obtained were characterized by spectrometry techniques, namely 1H NMR and MALDI-TOF, and the bacterial cellulose (BC) conductivity was assessed by means of four-point probe electrical conductivity technique. The best polymerization results were obtained with 5 mM AOT, 10 mM KHCF and 25 U/mL of laccase. The synergistic effect between both additives in the presence of catalyst lead to obtain BC samples coated with green polyaniline with promising electric conductive properties.